2018
DOI: 10.3390/molecules23051231
|View full text |Cite
|
Sign up to set email alerts
|

Density Functional Theory Applied to Excited State Intramolecular Proton Transfer in Imidazole-, Oxazole-, and Thiazole-Based Systems

Abstract: Excited state intramolecular proton transfer (ESIPT) is a photoinduced process strongly associated to hydrogen bonding within a molecular framework. In this manuscript, we computed potential energy data using Time Dependent Density Functional Theory (TDDFT) for triphenyl-substituted heterocycles, which evidenced an energetically favorable proton transfer on the excited state (i.e., ESIPT) but not on the ground state. Moreover, we describe how changes on heterocyclic functionalities, based on imidazole, oxazole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 87 publications
1
22
0
Order By: Relevance
“…The hydroxy group in 15 d was located in the position close to the nitrogen atom of the thiazole ring. Intermolecular hydrogen‐bonding interaction was not observed, but the bond length of N1−H21 was 1.891 Å, which suggested that ESIPT was expected to take place with 15 d . The presence of the intramolecular hydrogen‐bonding interactions is further supported by 1 H NMR spectra.…”
Section: Figurementioning
confidence: 93%
“…The hydroxy group in 15 d was located in the position close to the nitrogen atom of the thiazole ring. Intermolecular hydrogen‐bonding interaction was not observed, but the bond length of N1−H21 was 1.891 Å, which suggested that ESIPT was expected to take place with 15 d . The presence of the intramolecular hydrogen‐bonding interactions is further supported by 1 H NMR spectra.…”
Section: Figurementioning
confidence: 93%
“…Non‐normalized fluorescence (FL) spectra ( λ ex = 296 nm) for 1 (top, black line) and 2 (bottom, black line), compared to 2 − at different HO − concentrations (colored lines). In MeOH at 25°C; = 3.22 × 10 −5 mol L −1 ; using KOH as hydroxide source; [HO − ] = 0.64 (A), 2.63 (B) and 6.45 (C) mmol L − 1 …”
Section: Discussionmentioning
confidence: 99%
“…The triphenylimidazole structural framework has been intensely studied throughout the years, by many different research groups, due to its fluorescence (FL) and chemiluminescence (CL) properties. The typical direct CL of 2,4,5‐triphenylimidazole (also known as lophine) with oxygen in an alkaline media, first described by Radziszewski in 1877, was studied mainly to elucidate its reaction mechanism .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most remarkable photophysical property of the ESIPT chromophores is the large fluorescence Stokes shift. The presence of this property in compounds showing ESIPT phenomena, together with the dual emission makes them quite exploited as OLED materials, spectroscopy tools, and fluorescence probes in biology [ 9 , 10 , 11 , 12 , 13 ]. However, the ESIPT process in 2-acetyl-1-naphthol has been in controversy for long, primarily because of its quantitative ESIPT conversion in most solution conditions and also due to small Stokes shift of the ESIPT products (keto type prototautomer) compared to those products in other typical ESIPT molecules [ 1 , 14 ].…”
Section: Introductionmentioning
confidence: 99%